Comparative evaluation of different doses of ciprofloxacin alone and in combination with sulfasalazine in experimentally induced inflammatory bowel disease in rats - Parashuram, Shivashankar; Krishna, Purushotham; Lahkar, Mangala (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Inflammatory bowel disease (IBD) is an idiopathic, chronic inflammatory condition, which affects the gastrointestinal tract and has no curative treatment. The present study aimed to investigate the effect of different doses of ciprofloxacin alone and in combination with sulfasalazine in AA (acetic acid)-induced inflammatory bowel disease (IBD) in rats. Methods: A total of 36 animals were included in the study. Animals were divided into five groups (n = 6): group I - control (normal saline), group II-AA+ normal saline, group III-sulfasalazine(360mg/kg) +AA, group IV A - ciprofloxacin (50 mg/kg), group IV B- ciprofloxacin 100 mg/kg + AA, group V - ciprofloxacin 100 mg/kg + sulfasalazine (360 mg/kg) +AA. Group IV was divided into two subgroups, namely IVA and IVB, on the basis of different doses of ciprofloxacin used. After completion of two weeks of treatment, rats were sacrificed under ether anaesthesia for assessment of intestinal inflammation using parameters namely colon weight change, macroscopic and histopathological evaluation. Results: There was a decrease in colonic weight, macroscopic scores and microscopic scores in groups treated with ciprofloxacin at a dose of 100 mg/kg i.e. high dose given alone and in combination with sulfasalazine. Combination treatment was more effective when compared to single drug treatment. Conclusions: The present study indicates the efficacy of ciprofloxacin in acetic acid-induced IBD. The effects are more pronounced at higher dose i.e., 100 mg/kg. Combination of ciprofloxacin and sulfasalazine has shown greater efficacy than single drug treatment.